Music, a fundamental discipline (Journal of Parents and Teachers, 2026)
Music is an essential discipline for human development. This article features various testimonials from great teachers who explain how rhythm is present from the moment we are in the womb and the importance of integrating musical practice into both family and school life as a means of cohesion and expression.
Keywords: Music, development and expression.